PERAN BAITUL MAL WAT TAMWIL UNTUK PEMULIHAN EKONOMI NASABAH KORBAN GEMPA DI GANTIWARNO KLATEN - Sholahuddin, Muhammad (Benefit, 2010)
The aims of this research are to get a clear description about the role, supporting factors and constraint factors of BMT âSuryaâ toward a societies empowerment in the agriculture sector in Klaten. Related with the aims of the research, therefore this this case study used qualitative research. Method of collecting the data used In Deep Interview throught three ways, those are observating, interviewing and documentating. Technique of analizing the data used Miles-Huberman.Â  The result of this research are: (1) The role of Baitul Maal Wat Tamwil (BMT) âSuryaâ is empowerment of realized through services product by BMT âSuryaâ those are: (a) loan of agriculture sector (b) loan of livestock sector (c) loan of service sector and (d) loan of convection sector (2) supporting factors toward societies empowerment of economical sector in Klaten are: (a) strategic area (b) having closed emotional between the manager of BMT âSuryaâ and their clients, (c) developing relatieves atmosphere event itâs still prioriting the professionalism (3) constraint factors toward societies empowerment of economical sector in Klaten are: (a) They have only local network (b) there is a clients who get stuck in the process of pay in installments (c) pay in installments which is not appropriate with the loan.